Method for improving wear resistance of special recombinant material for independent liquid cargo tanks of LNG, LPG and LEG ships
Through the wood spin cutting, glue hot pressing and nano-enhanced treatment of LNG marine special recombinant materials, combined with the pad to reduce friction, the wear resistance problem of LNG ships in harsh environments is solved, and the durability and reliability of the material are improved.
Patent Information
- Application Number
- CN202510462527.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-14
- Publication Date
- 2025-07-08
AI Technical Summary
The prior art is difficult to effectively improve the wear resistance of LNG marine special recombinant materials under ultra-low temperature, high load and high friction conditions, resulting in insufficient durability and reliability.
Specific wood is rotary cut into veneer, and after applying glue to dry, hot pressing it into cargo holder wood, and nano-reinforced particles are introduced on the surface, combined with isocyanate adhesive protection to form a nano-wear-resistant layer. At the same time, a pad is placed between the upper and lower special recombinant materials to reduce the friction coefficient.
It significantly improves the wear resistance and structural integrity of special recombinant materials under ultra-low temperature, high load and high friction conditions, and meets the durability and reliability requirements of modern LNG ships for materials.
Smart Images

Figure CN120269659A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wood processing, and in particular to a method for improving the wear resistance of special recombinant materials used in independent liquid cargo tanks of LNG, LPG and LEG ships. Background Art
[0002] As global energy demand continues to grow, liquefied natural gas (LNG) is an efficient and clean energy source that is increasingly being used, and global trade volume is also rising year by year. Small and medium-sized LNG ships used for secondary transshipment usually use C-type independent liquid cargo tanks. In the C-type independent liquid cargo tank system, the horizontally arranged liquid cargo tanks are supported by supports.
[0003] The support is mainly composed of a fixed saddle and a sliding saddle. The fixed saddle is used to fix the position of the cargo tank and the hull, and the sliding saddle is mainly used to allow the tank to move freely within a certain range when the hull is under load or the temperature changes, so as to reduce the stress concentration caused by thermal expansion and contraction and hull deformation. The sliding saddle is equipped with upper and lower parts of special recombinant materials, which are fixed by small baffles located on the support panel and the tank cylinder respectively. LNG ships operate for a long time in harsh marine environments, especially under high load and high friction working conditions. The special recombinant materials at the sliding saddle face severe wear resistance challenges.
[0004] Traditional methods to improve the wear resistance of artificial board surfaces mostly focus on improving surface coatings or applying melamine impregnated paper, etc. However, these methods are often difficult to effectively maintain their wear resistance and structural integrity when faced with continuous friction under ultra-low temperature and high load conditions.
[0005] Therefore, how to improve the wear resistance of special recombinant materials for LNG ships under ultra-low temperature, high load and high friction conditions to meet the durability and reliability requirements of modern LNG ships has become an important issue that needs to be solved urgently. Summary of the invention
[0006] The present invention provides a method for improving the wear resistance of special recombinant materials for independent liquid cargo tanks of LNG, LPG and LEG ships, so as to solve the defect that the special recombinant materials at the sliding saddle in the prior art are difficult to meet the wear resistance requirements under ultra-low temperature and high load conditions, and can further improve the durability and reliability of the special recombinant materials.
[0007] The present invention provides a method for improving the wear resistance of a special recombinant material for an independent liquid cargo tank of an LNG, LPG or LEG ship, comprising the following steps: Select specific wood and peel it into veneer; The veneer is dried, glued and dried twice, then assembled and hot pressed to obtain a cargo hold support wood, the density of which is 1.30-1.38 g / cm3 ; During or after the preparation of the cargo hold bearer timber, nano-enhanced particles are introduced onto the outer surface of the surface veneer to obtain a special recombinant material; A backing plate is provided between the upper and lower parts of the special recombinant material to reduce the friction coefficient therebetween.
[0008] According to a method for improving the wear resistance of a special recombinant material for independent liquid cargo holds of LNG, LPG, and LEG ships provided by the present invention, the wood is selected from at least one of birch or beech, and the thickness of the veneer is 0.8 - 3.6 mm.
[0009] According to a method for improving the wear resistance of a special recombinant material for independent liquid cargo holds of LNG, LPG, and LEG ships provided by the present invention, the sizing amount of the veneer is 15 - 50%, and the moisture content after secondary drying is 6 - 8%.
[0010] According to a method for improving the wear resistance of a special recombinant material for independent liquid cargo holds of LNG, LPG, and LEG ships provided by the present invention, the nano-enhanced particles include at least one of nano-silica, nano-alumina, and nano-calcium carbonate.
[0011] According to a method for improving the wear resistance of a special recombinant material for independent liquid cargo holds of LNG, LPG, and LEG ships provided by the present invention, the hot pressing adopts segmented hot pressing, including the following steps: Maintain at 6 MPa and 70 °C for 60 min; then maintain at 12 MPa and 100 °C for 30 min; finally maintain at 140 °C and 16 MPa for 60 min.
[0012] According to a method for improving the wear resistance of a special recombinant material for independent liquid cargo holds of LNG, LPG, and LEG ships provided by the present invention, the step of introducing the nano-enhanced particles includes: After the surface veneer is impregnated and dried, it is laid flat; The prepared nano-enhancing agent is evenly sprayed onto the outer surface of the surface veneer; After the solvent in the nano-enhancing agent volatilizes, the surface veneer is assembled and hot pressed.
[0013] According to a method for improving the wear resistance of a special recombinant material for independent liquid cargo holds of LNG, LPG, and LEG ships provided by the present invention, an isocyanate adhesive is coated on the outer surface of the cargo hold bearer timber after hot pressing balance treatment to protect the nano-enhanced particles; Preferably, the nano-enhancing agent is obtained by mixing a volatile solvent and nano-particles; Preferably, the application amount of the nano-enhancing agent is 1.5 - 3.0 g / m 2 .
[0014] A method for improving the wear resistance of special recombinant materials for independent cargo tanks of LNG, LPG, and LEG ships according to the present invention. The step of introducing the nano-enhanced particles includes: After the cargo hold sill is prepared, clean and polish the outer surface of the cargo hold sill. Uniformly coat the prepared nano-enhancer on the outer surface of the cargo hold sill. Cure the nano-enhancer under preset conditions to form a nano-wear-resistant layer containing the nano-enhanced particles.
[0015] A method for improving the wear resistance of special recombinant materials for independent cargo tanks of LNG, LPG, and LEG ships according to the present invention. The preparation step of the nano-enhancer includes: Perform an anti-agglomeration surface treatment on the nano-particles. Mix the surface-treated nano-particles with the matrix material evenly to obtain a nano-composite material. Place the nano-composite material in a vacuum environment for degassing treatment to obtain a nano-enhancer. Preferably, the degassing treatment time is 10 to 15 minutes. Preferably, the addition amount of the nano-particles is 1% to 5% of the matrix material. Preferably, the application amount of the nano-enhancer is 80 to 120 g / m 2 .
[0016] According to the present invention, a method for improving the wear resistance of special recombinant materials for independent cargo tanks of LNG, LPG, and LEG ships, the backing plate is a thin stainless steel sheet.
[0017] Beneficial effects: An embodiment of the present invention provides a method for improving the wear resistance of special recombinant materials for independent liquid cargo tanks of LNG, LPG and LEG ships. A cargo hold support wood with a higher density is less likely to deform when subjected to high loads, thereby providing the special recombinant material with a more excellent load resistance and reducing the wear caused by deformation of the support wood; nano-reinforced particles with high hardness and excellent wear resistance can strengthen the microstructure of the cargo hold support wood through interface bonding, thereby improving the compressive strength and hardness of the surface of the cargo hold support wood, significantly enhancing its ability to resist high-load impact, and the higher bonding force and interface stability can effectively reduce the delamination or peeling of the nano-reinforced particles caused by thermal stress in ultra-low temperature environments. At the same time, the high stiffness and low friction coefficient of the nano-reinforced particles can greatly reduce the friction coefficient of the outer surface of the cargo hold support wood, thereby significantly reducing its adhesive wear, abrasive wear and fatigue peeling under high load conditions; in addition, the pad arranged between the upper and lower parts of the special recombinant material can reduce the friction coefficient between the two, thereby reducing wear. Compared with related technologies, it can effectively improve the wear resistance and structural integrity of special recombinant materials under ultra-low temperature, high load and high friction conditions, thereby meeting the durability and reliability requirements of modern LNG ships for materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 It is a structural schematic diagram of a sliding saddle structure provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] In order to better understand the method for improving the wear resistance of special recombinant materials for independent liquid cargo tanks of LNG, LPG and LEG ships provided by the embodiment of the present invention, its application background is first introduced. As an efficient and clean energy source, liquefied natural gas is increasingly widely used. LNG ships are special ships specially used to transport liquefied natural gas. Small and medium-sized LNG ships used for secondary transshipment usually use C-type independent liquid cargo tanks. In the C-type independent liquid cargo tank system, supports are used to support the horizontally longitudinally arranged liquid cargo tanks.
[0022] The support is mainly composed of a fixed saddle and a sliding saddle. The sliding saddle is equipped with two parts of special recombinant materials, which are fixed by small baffles on the support panel and the liquid cargo tank cylinder, respectively, so that the tank can move freely within a certain range. LNG ships operate for a long time in harsh marine environments, especially under high load and high friction working conditions, and the special recombinant materials at the sliding saddle face severe wear resistance challenges.
[0023] In the related art, the methods to improve the surface wear resistance of special recombinant materials are mostly focused on improving the surface coating or applying melamine impregnated paper, etc. However, these methods are often difficult to effectively maintain their wear resistance and structural integrity when facing continuous friction under ultra-low temperature and high load conditions.
[0024] Therefore, how to improve the wear resistance of special recombinant materials for LNG ships under ultra-low temperature, high load and high friction conditions to meet the durability and reliability requirements of modern LNG ships has become an important issue that needs to be solved urgently.
[0025] In the above-mentioned application context, an embodiment of the present invention provides a method for improving the wear resistance of special recombinant materials for independent liquid cargo tanks of LNG, LPG and LEG ships, which can effectively improve the wear resistance of special recombinant materials under ultra-low temperature, high load and high friction conditions to meet the durability and reliability requirements of modern LNG ships for materials.
[0026] Combine the following Figure 1 A method for improving the wear resistance of a special recombinant material for independent liquid cargo tanks of LNG, LPG and LEG ships provided by an embodiment of the present invention is described.
[0027] First of all, it should be pointed out that the experimental raw materials used in the following embodiments of the present invention, unless otherwise specified, can be purchased on the market or obtained according to conventional methods well known to those skilled in the art. All equipment involved, unless otherwise specified, are common equipment in the field and can be operated by those skilled in the art according to common industry knowledge and technical means.
[0028] A method for improving the wear resistance of special recombinant materials for independent liquid cargo tanks of LNG, LPG and LEG ships comprises the following steps: Step S10: Select specific wood and peel it into veneer.
[0029] In one embodiment of the present invention, the above-mentioned wood is selected from at least one of birch and beech, and the thickness of the veneer is 0.8-3.6 mm.
[0030] Step S20: After drying, gluing and secondary drying, the veneer is assembled and hot-pressed to obtain cargo hold support wood, the density of which is 1.30-1.38 g / cm 3 .
[0031] Specifically, after the wood is peeled into veneers, the veneers are dried, glued and dried again. The glue amount of the veneers is 15-50%, and the moisture content after secondary drying is 6-8%.
[0032] After the veneer is dried and glued, the veneer is assembled and hot pressed. In one embodiment of the present invention, the hot pressing adopts a segmented hot pressing process, which specifically includes the following steps: First, maintain the temperature at 6MPa and 70℃ for 60min to ensure that the adhesive fully infiltrates the material and eliminates bubbles and voids.
[0033] Then keep it at 12MPa and 100℃ for 30min to make the material layers fit tightly and the adhesive evenly distributed to prevent insufficient flow or premature curing.
[0034] Finally, the temperature is maintained at 16MPa and 140℃ for 60min to complete the densification and curing of the cargo hold support wood at high temperature, thereby improving the strength and density of the final product.
[0035] The density of the cargo hold wood obtained by the above scheme is 1.30-1.38g / cm 3 .
[0036] Specifically, the cargo hold support timbers produced by the above scheme have higher density than those of the prior art. The cargo hold support timbers with higher density and hardness are less likely to deform when subjected to high loads, thereby providing the special reconstructed materials with better load resistance and reducing the wear caused by deformation of the cargo hold support timbers.
[0037] It should be pointed out here that the segmented hot pressing process can be completed using an existing hot press machine. The specific structure and working principle of the hot press machine can refer to the existing technology and will not be described in detail in the embodiments of the present invention.
[0038] Step S30: During or after the preparation of the cargo hold support wood, nano-reinforced particles are introduced into the outer surface of the surface veneer to obtain a special recombinant material.
[0039] In some alternative embodiments, the nano-enhanced particles can be introduced before or after the preparation of the cargo hold sill. Specifically, the choice can be made in combination with the actual requirements and working scenarios.
[0040] In one embodiment of the present invention, the nano-enhanced particles are introduced before the preparation of the cargo hold sill is completed.
[0041] Specifically, after the surface veneer is impregnated with glue and dried, it is laid flat. Then, the prepared nano-enhancer containing nano-particles is evenly sprayed on the outer surface of the surface veneer by spraying. Only one side of each surface veneer that is used to form the outer surface of the cargo hold sill is sprayed. After the solvent in the nano-enhancer volatilizes, the blank is assembled and hot-pressed.
[0042] Specifically, the above-mentioned nano-enhancer is obtained by mixing a volatile solvent and nano-particles. In order to ensure that the nano-particles are evenly dispersed in the volatile solvent, methods such as ultrasonic treatment and mechanical stirring can be used to prevent agglomeration. In the nano-enhancer, the volatile solvent includes but is not limited to ethanol, and the nano-particles include but are not limited to nano-silica, nano-aluminum oxide, etc. The ratio of the volatile solvent to the nano-particles can be configured according to actual needs and is not specifically limited in the embodiments of the present invention. In order to ensure the performance of the nano-wear-resistant layer, the application amount of the nano-enhancer is 1.5 - 3.0 g / m 2 。
[0043] Specifically, a layer of isocyanate adhesive is further coated on the outer surface of the cargo hold sill after the hot-pressing and balancing treatment to protect the nano-wear-resistant layer and improve its performance.
[0044] In another embodiment of the present invention, the nano-wear-resistant layer is introduced after the preparation of the cargo hold sill is completed.
[0045] Specifically, after the preparation of the cargo hold sill is completed, the outer surface of the cargo hold sill is cleaned and polished to ensure the adhesion of the nano-enhancer. Then, the prepared nano-enhancer is evenly coated on the outer surface of the cargo hold sill, and the nano-enhancer is cured under preset conditions to finally form a nano-wear-resistant layer containing nano-enhanced particles.
[0046] Specifically, when preparing the above-mentioned nano-enhancer, the nano-particles are first subjected to anti-agglomeration surface treatment to enhance the dispersibility and interfacial compatibility of the nano-particles and prevent agglomeration. Based on different action principles, the surface treatment methods can include chemical methods (such as coupling agent modification, graft copolymerization, surfactant coating, etc.) and composite methods (such as multi-layer coating, self-assembled monolayer, etc.), and the specific choice can be made according to actual needs and is not specifically limited in the embodiments of the present invention.
[0047] After the anti-agglomeration surface treatment, the nanoparticles are mixed with a matrix material (such as epoxy resin). Specifically, the addition amount of the nanoparticles is 1% - 5% of the matrix material. And to reduce the viscosity of the matrix material, the mixing temperature is raised to 95°C. To promote the dispersion of the nanoparticles, physical dispersion machinery such as a high-shear mixer or an ultrasonic disperser can be used. The mixture is kneaded in a high-mixing device for 20 minutes to obtain a nanocomposite material. Then, the mixed nanocomposite material is placed in a vacuum environment for degassing treatment to remove the air introduced during the mixing process, ensuring the quality and performance of the final nano-enhancer and reducing the impact of air bubbles on the mechanical properties and surface quality of the nano-wear-resistant layer. The degassing treatment time is about 10 - 15 minutes, and the nano-enhancer is obtained after degassing.
[0048] After the nano-enhancer is prepared, the nano-enhancer is uniformly applied to the outer surface of the cargo hold bearer by an appropriate coating method, such as spraying or brushing. The coating amount is 80 - 120 g / m 2 . After the coating is completed, a curing treatment is carried out to form a firm nano-wear-resistant layer containing nano-enhancing particles. According to the characteristics of different matrix materials, appropriate curing temperature and time can be selected. For example, when using epoxy resin as the matrix material, it can be cured at 80°C for 2 hours or cured at room temperature for 24 hours to finally form a firm nano-wear-resistant layer.
[0049] Step S40: A backing plate is arranged between the upper and lower parts of the special recombination material to reduce the friction coefficient between the two.
[0050] Specifically, after the special recombination material is prepared, the upper and lower parts of the special recombination material make the tank move freely within a certain range through sliding contact to reduce the stress concentration caused by thermal expansion and contraction and hull deformation. By the backing plate arranged between the upper and lower parts of the special recombination material, the friction coefficient between the two can be reduced, thereby reducing wear.
[0051] In one embodiment of the present invention, the backing plate is made of a thin stainless steel sheet.
[0052] It can be understood that the backing plate is not limited to the materials listed above. Other materials of the backing plate that can meet the required strength and friction coefficient are equally applicable, and are not listed in the embodiments of the present invention.
[0053] It can be understood that, without contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples.
[0054] Through the method for improving the wear resistance of special recombinant materials for independent liquid cargo tanks of LNG, LPG and LEG ships provided by the embodiment of the present invention, cargo hold support timbers with higher density are less likely to deform when subjected to high loads, thereby providing the special recombinant materials with more excellent load resistance and reducing the wear caused by deformation of the support timbers; nano-reinforced particles with high hardness and excellent wear resistance can strengthen the microstructure of the cargo hold support timbers through interface bonding, thereby improving the compressive strength and hardness of the surface of the cargo hold support timbers, significantly enhancing their ability to resist high-load impacts, and the higher bonding force and interface stability can effectively reduce the delamination or peeling of the nano-reinforced particles caused by thermal stress in ultra-low temperature environments. At the same time, the high stiffness and low friction coefficient of the nano-reinforced particles can greatly reduce the friction coefficient of the outer surface of the cargo hold support timbers, thereby significantly reducing its adhesive wear, abrasive wear and fatigue spalling under high-load conditions; in addition, the pad arranged between the upper and lower parts of the special recombinant material can reduce the friction coefficient between the two, thereby reducing wear. Compared with related technologies, it can effectively improve the wear resistance and structural integrity of special recombinant materials under ultra-low temperature, high load and high friction conditions, thereby meeting the durability and reliability requirements of modern LNG ships for materials.
[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for improving the wear resistance of special recombinant materials for independent cargo tanks of LNG, LPG, and LEG ships, characterized in that, It includes the following steps: Select specific wood and veneer it into veneers; The veneer is dried, sized, and then dried again, followed by assembling and hot pressing to obtain the cargo hold bearing wood. The density of the cargo hold bearing wood is 1.30 - 1.38 g / cm 3 ; During or after the preparation of the cargo hold bearing wood, introduce nano-enhanced particles onto the outer surface of the surface veneer to obtain a special recombinant material; Lay a backing plate between the upper and lower parts of the special recombinant material to reduce the friction coefficient between the two.
2. The method according to claim 1, wherein The wood is selected from at least one of birch or beech, and the thickness of the veneer is 0.8 - 3.6 mm.
3. The method according to claim 1, characterized in that, The sizing amount of the veneer is 15 - 50%, and the moisture content after secondary drying is 6 - 8%.
4. The method according to claim 1, wherein The nano-enhanced particles include at least one of nano-silica, nano-alumina, and nano-calcium carbonate.
5. The method according to claim 1, wherein The hot pressing adopts segmented hot pressing and includes the following steps: Maintain at 6 MPa and 70 °C for 60 min; then maintain at 12 MPa and 100 °C for 30 min; finally maintain at 140 °C and 16 MPa for 60 min.
6. The method according to claim 1, wherein The step of introducing the nano-enhanced particles includes: After the surface veneer is impregnated with glue and dried, lay it flat; Evenly spray the prepared nano-enhancing agent on the outer surface of the surface veneer; After the solvent in the nano-enhancing agent volatilizes, perform blanking and hot pressing on the surface veneer.
7. According to the method described in claim 6, wherein, Coat the outer surface of the cargo hold bearing wood after hot pressing balance treatment with an isocyanate adhesive to protect the nano-enhanced particles; Preferably, the nano-enhancing agent is obtained by mixing a volatile solvent and nano-particles; Preferably, the application amount of the nano-enhancer is 1.5 to 3.0 g / m 2 .
8. The method according to claim 1, wherein The step of introducing the nano-enhanced particles includes: After the cargo hold bearing wood is prepared, clean and polish the outer surface of the cargo hold bearing wood; Evenly coat the prepared nano-enhancing agent on the outer surface of the cargo hold bearing wood; Under preset conditions, perform a curing treatment on the nano-enhancing agent to form a nano-wear-resistant layer containing the nano-enhanced particles.
9. The method according to claim 8, wherein The preparation step of the nano-enhancing agent includes: Perform an anti-agglomeration surface treatment on the nano-particles; Mix the surface-treated nano-particles and the matrix material evenly to obtain a nano-composite material; Place the nano-composite material in a vacuum environment for degassing treatment to obtain a nano-enhancing agent; Preferably, the addition amount of the nano-particles is 1% - 5% of the matrix material; Preferably, the application amount of the nano-enhancer is 80-120 g / m 2 .
10. According to the method described in any one of claims 1 to 9, wherein, The backing plate is a thin stainless steel sheet.
Citation Information
Patent Citations
Wearproof wooden floor
CN101666155A
Spraying process for non-sticky coating of elevator or escalator surface
CN102861711A
Special recombined material for independent liquid cargo tanks of LNG, LPG and LEG ships and manufacturing method of special recombined material
CN119388536A
Benzvalene form sliding friction - roller bearing rolling friction makes up isolation bearing
CN205000238U
Polyvinyl chloride composite floor
CN217027881U